Pendapat Orang Tua Murid Sekolah Tentang Komunikasi Pembelajaran Pasca Gempa Cianjur 2022 - Herta A. Soemardjo; Chendi Liana; Abdul Harif Siswanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Cianjur 2022 earthquake following the COVID-19 pandemic, made it necessary for the schools at Legok Nangka and Liung Tutut, Cugenang, Cibeureum, Cianjur, to have a full then partly on line teaching and learning system for their students. Observing the children’s enthusiasm to learning activities while accompanying them at a trauma healing activity not long after the earthquake, drew us to come back to these villages to find out about teaching and learning activities in this area. This study is to find out about the opinion of the students’ parents about the effectiveness of the post-earthquake learning activities. Theory used to explain this study is the Theory of Process of Communications by Harold D Laswell, which says that communication is about ‘who says what to whom through which channel with what effects.’ Research methods used is quantitative descriptive, and data was collected through distributing questionnaires and interviews to some mothers and students. The research population was mothers of primary and secondary school students living at Legok Nangka and Liung Tutut, Cugenang, Cibeureum, Cianjur. Sampling methods used was total sampling. The result of this study was that according to mothers of primary and secondary school living in these villages, the effectiveness of teaching and learning activities until August, even December 2023 (for some schools) was still low, since learning facilities has not yet being fully recovered after the Cianjur earthquake and other obstacles. It was not advised to imply online teaching and learning activities for school students, especially at villages where the educational background of parents is low.